Bap concentration and tetraploid banana micropropagation efficiency (AAAB group) (Scientia Agricola, 2001)
The objective of the present work was to establish an efficient procedure for the in vitro production of tetraploid banana plantlets (Musa sp. cv. FHIA-01, AAAB group). The cloning effect on the in vitro development of the explants, the rates of contamination and multiplication, and the level of oxidation in culture media with five benzylaminopurine (BAP) concentrations were studied. In the phase of in vitro introduction of explants, a high level of contamination (22.32%), caused mainly by bacteria, was observed. However, the degree of contamination decreased along the subcultures, reaching 1.07% in the eighth subculture. Higher multiplication rates were obtained, averaging 2.65 per subculture, on the MS media supplemented with 4.0 mg L-1 BAP, leading to an estimated production of 584 and 3451 plantlets/initial explant after the 6th and 8th subculture, respectively. A pronounced effect of the cloning on multiplication was observed. Acclimatization efficiency of plantlets was 94%. Somaclonal variations were not observed among in vitro micropropagated plantlets under greenhouse conditions.